2021
DOI: 10.1245/s10434-021-10316-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of County-Level Racial Diversity and Likelihood of a Textbook Outcome Following Pancreas Surgery

Abstract: Introduction Residential racial desegregation has demonstrated improved economic and education outcomes. The degree of racial community segregation relative to surgical outcomes has not been examined. Patients and Methods Patients undergoing pancreatic resection between 2013 and 2017 were identified from Medicare Standard Analytic Files. A diversity index for each county was calculated from the American Community Survey. Multivariable mixed-effects logistic regression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…We chose TO as our primary outcome because composite measures often provide more comprehensive assessments of surgical outcomes than single variables. 40 42 Our data demonstrate the utility of this approach. While all component variables had increased aOR for Medicare and Medicaid/Uninsured patients compared to the Private insurance group (Table 3 ), only CDIV complications were significant for Medicare and 30-day EDOS and readmissions for Medicaid/Uninsured patients.…”
Section: Discussionsupporting
confidence: 57%
“…We chose TO as our primary outcome because composite measures often provide more comprehensive assessments of surgical outcomes than single variables. 40 42 Our data demonstrate the utility of this approach. While all component variables had increased aOR for Medicare and Medicaid/Uninsured patients compared to the Private insurance group (Table 3 ), only CDIV complications were significant for Medicare and 30-day EDOS and readmissions for Medicaid/Uninsured patients.…”
Section: Discussionsupporting
confidence: 57%
“…PP is associated with worse postoperative course following surgical resection. 29 Our research group has recently reported on the association of county‐level poverty duration relative to individual‐level cancer outcomes 10 . Duration of poverty was associated with lower odds of receipt of surgical treatment, achievement of textbook outcomes, and worse cancer‐specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…A high SVI was an independent predictor of complications and 90-day deaths after both pancreatic and liver surgery as well as prolonged LOS in liver surgery 17 . Socioeconomic factors independently associated with achievement of TO were lower patient education, government insurance, low county-level racial diversity, and Black race 6 , 18 , 24 , 27 .…”
Section: Resultsmentioning
confidence: 99%